Analisis Perlindungan Hukum Data Pribadi Nasabah Pada Transaksi Internet Banking Di Sulawesi Utara - Prayogo, Presly; Korah, Revy S.M; Soepeno, Mohammad Hero; Kasenda, Victor (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
Internet banking is one of the services created by general banking using internet technology, but it still requires legal certainty to protect the personal data of its customers. The research was then aimed at exploring more deeply the legal protection of personal data at one of the banks in North Sulawesi in a normative way. customers use these banking services. By searching the legal literature, laws and regulations from related agencies, the primary sources are complemented by in-depth interviews with informants at bank locations. The end of the research concluded that the bank had made every effort to comply with Indonesian legal provisions by making transactions via internet banking supported by strict supervision from the competent authorities.